2018
DOI: 10.1002/cnma.201800357
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Stable Inorganic Perovskite Quantum Dots by Embedding into a Polymer Matrix

Abstract: All‐inorganic perovskite quantum dots (QDs) with high photoluminescence quantum yield, narrow spectral bandwidth, and broad spectral tunability have broad applications. However, perovskite QDs suffer from poor stability and the fast anion‐exchange reaction between different halide ions. Herein, we embedded green‐light‐emitting CsPbBr3 QDs and red‐light‐emitting CsPb(Br/I)3 QDs into carboxyl‐containing polymethyl methacrylate (PMMA) by the hot‐injection method. As a result, the as‐prepared perovskite@PMMA compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 45 publications
(76 reference statements)
2
23
0
Order By: Relevance
“…Among these methods, the coating technique is an effective method to enhance the optical performance and stability of NCs, which is due to their transparent characteristic, low cost, and the stability of coating components. Polymers, [ 34–40 ] metal‐organic frameworks [ 41,42 ] and inorganic shells [ 43–46 ] have been reported to improve the optical performance and stability of NCs. However, the coating techniques for NCs are found to lead to the uncontrolled morphologies and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, the coating technique is an effective method to enhance the optical performance and stability of NCs, which is due to their transparent characteristic, low cost, and the stability of coating components. Polymers, [ 34–40 ] metal‐organic frameworks [ 41,42 ] and inorganic shells [ 43–46 ] have been reported to improve the optical performance and stability of NCs. However, the coating techniques for NCs are found to lead to the uncontrolled morphologies and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…However, once water and oxygen permeate through the polymer, the perovskite film would degrade very fast. [ 16,17 ] Therefore, the inherently stable quasi‐2D perovskites exhibit huge potential for stable and highly efficient optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that when the QDs-CsPbBr 3 solution was doped with various ratios of PMMA solution, the location of the PL peak barely shifted. This means that the PMMA does not influence the band structure of the QDs-CsPbBr 3 , but surrounds and protects the QDs-CsPbBr 3 to stabilize the material structure [41,42].…”
Section: Resultsmentioning
confidence: 99%